Teacher attachment and intention of aggressive behaviour among school children - Duru, Chidiebere Kelechi; Redzuan, Ma'rof; Hamsan, Hanina Halimatusaadiah; Shahrimin, Mohd. Ibrani (International Organization of Scientific Research, 2015)
The main purpose of this study was to determine the relationships between teacher attachment and intention to aggressive behavior among school children. This study involved 426 school children using self-administered questionnaire from six government daily secondary schools. The school children were selected using simple random sampling method. Respondents were males (199) and females (227) between 13-17 years old. Teacher attachment was measured using inventory of parents attachment (IPPA) with respect to teacher attachment and intention of aggressive behavior. Pearson's correlation analysis revealed that there is a significant with negative weak relationship between teacher attachment and school children intention of aggressive behavior (r=-0.126, p<0.05). Also the result of t-test analysis showed that there is no significant difference between male and female school children in term of intention of aggressive behavior (t=1.050:p=0.294). Moreover, the relationship indicates that lack of teachers monitoring and cooperation influence student to engage in intention of aggressive behavior. It is recommended that policy makers and school counselors should give more emphasis on the improvement of good and suitable environment in the school to improve children satisfaction in the school environment and thus help improve their ability not to engage in aggressive behavior.